Clinical characteristics, prognosis and outcome of patients with repaired tetralogy of Fallot - Biljana Milinković; Dejan Bokonjić; Verica Prodanović (Биомедицинска истраживања, 2019)
Progress in diagnosis and treatment has led to a significant improvement in the fate of children born with tetralogy of Fallot, with the perioperative mortality of 2-3% and a 30-year survival rate of 90%. However, the majority of these patients have residual postoperative morphological and hemodynamic disorders, as well as heart rhythm disorders, primarily due to the volume loading of the right ventricle caused by chronic pulmonary regurgitation. Improved surgical techniques have reduced early mortality to less than 3%, but the annual mortality rate has increased 20-30 years after initial surgical remediation, mainly due to unwanted cardiac events. In longitudinal monitoring of patients after repair of tetralogy of Fallot, early detection of morphological and hemodynamic residual disorders both in asymptomatic and symptomatic patients is of great importance. The purpose of this is a timely identification of new therapeutic measures (e.g. pulmonary valve replacement) in order to improve the course and outcome of treatment. Cardiovascular magnetic resonance imaging is a diagnostic method that provides the most precise and accurate estimation of individual parameters of cardiac dysfunction and poor outcomes. Furthermore, it plays a significant role in defining the predictive ability of individual parameters. Previous research has shown that the increase in mortality risk coincides with progressive dilation and right ventricular dysfunction, by means of ventriculo-ventricular interaction and left ventricular dysfunction. Identification of parameters that can predict the high-risk patients for future unwanted cardiac events such as ventricular tachycardia and cardiac insufficiency can assist the customization of a therapeutic approach leading to improvement in quality of life and patient's survival rate.
Keywords: tetralogy of Fallot; right ventricular dysfunction; cardiovascular magnetic resonance imaging; prognosis